Utilization of Produced Heat in Motorcycle Exhaust as a Mobile Battery Charger Using Thermoelectric Seebeck Generator - Naibaho, Eko; Tamba, Takdir (Talenta Publisher, 2021)
Produced heat from motorcycle exhaust has been used to recharge cellphone batteries using a thermoelectric seebeck generator and program settings from the Arduino microcontroller. This tool consists of an LM 35 sensor that functions as a temperature reader, TEG as a heat converter to voltage, DC to DC Booster as a voltage controller, Arduino Uno as a data processor, LCD as a display. The software in this tool uses the Arduino IDE program. This tool is used to convert heat into voltage. The working principle of this system in general is that when the exhaust heat is removed, the controller will read the data from the LM 35 temperature sensor. After that the data will be processed by the microcontroller. After obtaining the processed data, the result data is then displayed on the LCD and the relay circuit will activate the system when the required voltage is appropriate